2015 IEEE 13th International Symposium on Applied Machine Intelligence and Informatics (SAMI) 2015
DOI: 10.1109/sami.2015.7061900
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the change of flight, navigation and motor data visualization on psychophysiological state of pilots

Abstract: Psychological discomfort and stress may negatively affect various work activities especially in professions that are directly responsible for the lives and health of human beings. We can find these kinds of professions mainly in civil aviation, specifically the profession of a pilot. Analysis showed, that the legislative requirements for the qualifications of a pilot, require only the competence for a particular aircraft but they don't take in account the ergonomics of the cabin and the visualization of the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…For instance, Luque-Casado et al (2016) demonstrated a decrement in HRV values with time-on-task, which would be linked to vigilance decrement or mental fatigue under high cognitive demand. This concern has also been raised in other studies dealing with either training (e.g., Socha et al, 2015 suggest that pilots with more extensive training sessions exhibit lower values on the short-term power spectrum of ECG) or emotional habituation (Feda and Roemmich, 2016;Sevenster et al, 2015).…”
Section: Introductionmentioning
confidence: 94%
“…For instance, Luque-Casado et al (2016) demonstrated a decrement in HRV values with time-on-task, which would be linked to vigilance decrement or mental fatigue under high cognitive demand. This concern has also been raised in other studies dealing with either training (e.g., Socha et al, 2015 suggest that pilots with more extensive training sessions exhibit lower values on the short-term power spectrum of ECG) or emotional habituation (Feda and Roemmich, 2016;Sevenster et al, 2015).…”
Section: Introductionmentioning
confidence: 94%
“…also from the point of precision of piloting techniques. It means that by measuring pilot's load we are able to quantify pilot performance (for particular results, see [8,9]). For this purpose, the research project made use of measurement equipment of the Faculty of Biomedicine Engineering, CTU in Prague [10,11].…”
Section: Measuring Pilot Performance By Way Of Definingmentioning
confidence: 99%
“…It is thus vital to opt for compact wearable telemetry systems. An example of such application would be monitoring of pilots [10][11][12], in situations when it is impossible to measure physiological signals using standard medical devices due to their dimensions (e.g., ECG) in a plane cockpit. The importance of wearable telemetry systems capable of measuring and evaluating physiological condition and environmental parameters of the close surroundings of the user may be clearly seen with members of IRS (Integrates Rescue System).…”
Section: Introductionmentioning
confidence: 99%